Organic polymer doped graphene-based composite for the effective elimination of diclofenac: A detailed study with phytotoxic assessments. Issue 1 (February 2023) - Bedadeep, Das; Shahnaz, Tasrin; Manu Sankar, V.; Sahoo, Lingaraj; Narayanasamy, Selvaraju
Abstract: In recent years, diclofenac (DCF), a non-steroidal anti-inflammatory drug (NSAID), has become globally ubiquitous in various environments, most frequently detected in freshwater bodies posing potential toxic effects on aquatic and terrestrial life as well as human health. Considering the currently available processes to eliminate DCF, adsorption is one of the effective means for this purpose. In the current study, polypyrrole-doped reduced graphene oxide (GAP) was evaluated for the efficient removal of DCF from industrial wastewater. The incorporation of polypyrrole proved to augment the removal efficiency compared to the raw graphene oxide. In the optimisation of the process parameters, the removal efficiency of diclofenac using GAP was obtained to be 95.3 %. The adsorption process was found to be a good fit for the Freundlich isotherm and the pseud-second-order kinetics. The treated DCF aqueous solution using GAP has been evaluated for plant growth to determine the efficacy of the remediation process. The regenerative study indicated promising removal efficiency, demonstrating the excellent performance of GAP as an alternative to current adsorbents used for diclofenac removal from industrial wastewater. Graphical Abstract: ga1 Highlights: Polypyrrole doped graphene-based material was synthesized. Optimised removal of diclofenac was achieved by adsorption process. Isotherm, kinetics, and thermodynamics studies of the process were evaluated. Phytotoxic assessment of the process was performed.